HUBUNGAN HIERARKI BINATANG YANG TEREPRESENTASI DALAM PERIBAHASA BINATANG BAHASA MELAYU - Juyoung Lee (Faculty of Languages and Arts, Universitas Negeri Padang, 2020)
The aim of this study is to scrutinize the hierarchical relationships of animal groups represented in Malay animal proverbs. This study attempts to figure out the hierarchical relationships of animal groups to which relatively little attention have been paid so far, based on a metaphor or a conceptual mapping. To investigate the problem, this study takes advantage of Pusat Rujukan Persuratan Melayu (http://prpm.dbp.gov.my/) to collect Malay animal proverbs and analyzes it by using an axiological evaluation, that is, a positive value denotes a high rank. The result of this study provides a useful ground to understand the hierarchical relationships of animal groups concealed in the brain of Malay speakers and to savor Malay cultural identity.